Age and sex differences in problem behaviours in youth with autism spectrum disorder. (February 2023) - Graziosi, Gemma; Perry, Adrienne
Abstract: Background: Many youth with autism spectrum disorder (ASD) display problem behaviours. Although previous studies have examined age and sex differences in problem behaviours in youth with ASD, most have done so with samples that exhibited a limited range of adaptive or intellectual functioning. This study sought to examine age and sex differences in problem behaviours in youth with ASD who were diverse in age and developmental level. Method: Levels of problem behaviour, as measured by the Aberrant Behavior Checklist, were examined according to age, sex, and developmental level using data from 457 inpatients (4–20 years old; 94 females) enrolled in the SFARI Autism Inpatient Collection. Multiple regression analyses were conducted to determine the extent to which participant characteristics predict problem behaviours. Results: Age was somewhat negatively correlated with irritability and total problem behaviours and moderately negatively correlated with hyperactivity. Females exhibited significantly greater scores for irritability than males. Developmental level was negatively correlated with most problem behaviours. Age, sex, and developmental level in combination accounted for a small amount of variance in most problem behaviours. Conclusions: Specific problem behaviours in youth with ASD showed some age- and sex-related differences. Higher levels of problem behaviours were also associated with lower developmental level. The generalizability of these findings may be limited due to the sample consisting exclusively of inpatients. Nonetheless, recognizing differences in levels and types of problem behaviour among youth with ASD can be useful for the development and implementation of effective intervention strategies, especially in those with lower adaptive or intellectual functioning. Highlights: More severe problem behaviours are associated with younger age in youth with ASD. Females with ASD exhibit certain types of problem behaviours more severely than males. Lower developmental level is associated with more severe problem behaviours. Recognizing these differences in problem behaviours can inform intervention.